Pedagogic Competency and Readiness of Primary School Teachers in the Implementation of Curriculum 2013 - La Sisi; La Sarimu; Chairan Zibar L.Parisu (Jurnal Sultra Elementary School, 2020)
Abstract: Pedagogical Competence and Readiness of Primary School Teachers in Implementation of 2013 Curriculum, this study aims to analyze (1) elementary teacher pedagogic competencies in the implementation of the 2013 curriculum; (2) readiness of elementary school teachers in the implementation of the 2013 curriculum; (3) readiness of facilities and infrastructure to support learning; (4) 2013 learning planning curriculum developed by elementary school teachers; (5) implementation of 2013 curriculum learning by elementary teachers; and (6) 2013 curriculum level by elementary school teachers. This type of research is descriptive research. The type of data used in this study is quantitative and qualitative descriptive. The sample of this study was class I and IV teachers who studied 40 teachers. The sampling technique in this study used purposive sampling. The instruments used were written tests, questionnaires, observation sheets and documentation.               The results of the study show that (1) pedagogical competencies are based on test results with an average value of 56.25 according to sufficient categories; (2) teacher competence based on teacher questionnaires with an average score of 73.48 in good categories; (3) teacher preparedness based on a questionnaire with an average value of 62.85 included in the sufficient category; (4) readiness of learning facilities and infrastructure according to the observation guidelines with an average value of 79.3 in the good category; (5) learning plan based on learning outcomes with an average score of 73.42 in good categories; and (6) implementation of learning based on observation regulations with an average value of 69.57 in accordance with sufficient categories; 7) The value of the questionnaire based on the teacher with an average score of 63.75 is in the sufficient category. Keywords: Pedagogics, Competence, Readiness, Implementation, Curriculum